(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to demonstrate the impact of green computing on improving the value of the product by using one of its tools represented by recycling electronic waste. Many conclusions were reached, the most important of which is that the application of green computing will add value to the product by reducing product costs while maintaining the level of quality. Many recommendations were reached. The most important of which is that the Electronic Industries Company must adopt green computing to preserve the environment and reduce costs.